Factors Affecting MSME Actors' Interest In Becoming Customers For Islamic Bank Financing - Annisa Nur Istiqomah; Rafli Dwi Adiputra; Yenny Kornitasari (LPPM ISNJ Bengkalis, 2023)
This research aims to analyze the influence of Islamic financial literacy, capital requirements, ratios, and convenience on the interest of micro, small, and medium enterprises (MSMEs) to become Islamic bank financing customers. This research uses a descriptive quantitative approach with an analytical method such as multiple linear regression. The population of this research is all MSME actors in East Java. The research sample was obtained from 63 MSMEs in East Java using the Roscoe approach. The data source uses primary data as a questionnaire and is analyzed using multiple linear regression. The research results show that Islamic financial literacy, capital requirements, nisba, and convenience significantly influence the interest of MSMEs to become Islamic bank financing customers. Partially, only the nisba positively and significantly affects the interest of MSMEs to become Islamic bank financing customers. Islamic financial literacy, capital requirements, and convenience do not influence the interest of MSMEs to become Islamic bank financing customers. This research can be used as a complement to existing theories. It can be used as a reference for Islamic banks and the government in developing strategies to attract MSMEs to become Islamic bank financing customers.